Salmonella sp. em frango e ambiente de abate - Oliveira , Aline Pedrosa de (2012)
Poultry food products are identified as being important backers of Salmonella sp. and cause of salmonellosis, which can occur all over the world. In consequence of the impact of this agent to public health and the economy, its monitoring and control should be established in poultry slaughtering. In relevance has been observed the emergence of resistant strains isolated from food to antibiotics in treatment failures reflect the lack of effective response to the principle of the pathogen antimicrobial elected. In this context, the aim of this work was to verify the occurrence of Salmonella sp. in broilers slaughtered in 15 batches from four industries of the state of Goias. The plots were composed of six different samples of carcasses, hearts, gizzards, livers, defeathering and evisceration gutters, using the methods conventional bacterial isolation and enzyme immunoassay VIDAS® for investigation. The susceptibility profile of isolates was determined. Observed the occurrence of Salmonella sp. in 53.33% (8/15) of the lots analyzed and it was found that among the 300 samples analyzed, 21 (7%) were contaminated by the agent. Samples of heart and gizzard showed a higher positivity rate (8.90%), followed by carcass samples (8%), evisceration gutters (6.70%), liver and defeathering showed lower percentages of isolation (4.45 %). In all categories of samples was the isolation of the pathogen, which characterizes the presence of the agent in food and environment slaughter and processing of poultry products. The most frequently isolated serovar of Salmonella Schwarzengrund was (22.41%), followed by serovars Salmonella Cerro (20.69%) and Salmonella Typhimurium (20.69%), Salmonella Livingstone (10, 34%), Salmonella Infantis (5.17%), Salmonella Enteritidis (3.45%), Salmonella Mbandaka (3.45%), Salmonella Saintpaul (3.45%), Salmonella Anatum (1.72%), Salmonella O: 9.15 (1.72%), Salmonella Ohio (1.72%) and Salmonella reacted, but did not conform RDNC (5,17%). Profile of antimicrobial susceptibility, it was observed that 100% of the strains were resistant to erythromycin, 56,89% to nalidixic, 13,79% enrofloxacin, 6,90% to cefotaxime, 3,45% cephalothin and cefoxitin, none of the strains were resistant to sulfazotrim and chloramphenicol. It was observed that 35 (60.34%) were resistant to more than one rule, and one of the isolates was resistant to six of the eight principles antimicrobials. By this results, obtained by evaluated plots, it can concluded that poultry food “in natura” realeased to contain Salmonella consumption, it is also present in the environment of slaughter. This finding supports the need for monitoring food consumption and the environment slaughtering of broilers. Isolates strains denoted different profiles of susceptibility to antimicrobials, occurring multiple resistance and cross-resistance to be considered when evaluated the risk of pathogen in foods.